Basketball : step-by-step - Burns, Brian; Dunning, Mark, 1957- (New York : Rosen Central, 2010)
Step-by-step photographs and instructions demonstrate basic offensive and defensive skills for basketball players.
Includes bibliographical references (p. [92]-[94]) and index.
6.9
5-8
Keywords: Basketball -- Juvenile literature; Basketball; Basketball